Potential of adopting small scale postharvest practices towards reducing plantain supply chain food losses in Rivers State, Nigeria - Morris, Kwami Justina Kenobi (2017)
Postharvest losses (PHLs) is the most significant contributor of food losses in developing countries. High PHLs in food staples like plantain pose a threat to food security in Nigeria; therefore, viable strategies to reduce PHLs in agri-food supply chains is in dire need. Conventional postharvest technologies used in modern agrifood supply chains in developed countries require high capital investments and technological competence; most of which is lacking in Nigeria. Although, sophisticated postharvest technologies may not be within the reach of farmers and traders who operate in traditional supply chains, small-scale postharvest practices (SSPPs) such as shade-cooling, hydro-cooling, use of protective transport materials are simpler alternatives to help maintain produce quality, prolong shelf-life and consequently reduce PHLs. However, the adoption of these SSPPs is low and there is dearth of information in this regard. This study adopted a quantitative approach to investigate the potential adoption of selected SSPPs by plantain farmers and traders who operate in a traditional supply chain in Rivers State, Nigeria. The study intended to determine the influence of adoption factors on farmers and traders intention to use SSPPs. The data used in the study were obatained via face-to-face interviews using two structured questionnaire where one questionnaire was administered to farmers and the other one administered to the traders. The data were analysed using statistical techniques such as descriptive analyses, chi-square, mean ranking, T-test, Pearson’s correlation, and partial least square structural equation modelling. In terms of the losses, the findings of the study revealed that a significant amount of plantain comodity is entirely lost from the food supply chain; this is regarded as the quantitative losses. Furthermore, it was observed that more than half of the produce is reportedly sold at reduced prices due to quality deterioration; this form of losses was interpreted as the amount of qualitative losses. A correlation analysis revealed that use of small-scale postharvest practices had a significant negative relationship with the amount of self-reported quantitative and qualitative losses at both farm and market levels. With regards to adoption, the results of the chi-square analyses indicated that gender, education level, occupation, harvetsed produce and information sources were significantly associated with farmers adoption whereas experience level and information sources were the significant factors associated with the traders adoption of SSPPs. Based on the mean rankings, the respondents were observed to have low awareness and adoption rates for a majority of the postharvest practices investigated. In addition, the results of t-tests show that adopters demonstarted more positive perceptions of the SSPPs than non-adopters. Furthermore, an exploratory factor analysis (EFA) revealed six and five factors as representing perceptions towards SSPPs perceptions towards each postharvest practice as relevant to farmers and traders repectively. This implies that when respondents evaluated the usefulness and complexity of a particular postharvest practice, they evaluated the practice as one entity rather than considering the perceived usefulness and ease of use of the postharvest practice as separate dimensions. Factor analysis of the items that measured behaviour towards adoption of SSPPs extracted three factors named as attitudes, motivation and intention. The EFA factor solutions were further confirmed during confirmatory factor analysis during which the measurement models were rigourosly assessed to ensure reliability and validity of constructs and scales. Assessment of the variables that influence farmers and traders potential to adopt SSPPs with intention to use postharvest practices as the dependent variable, the results of the structural equation modelling found that awareness level, perceptions, attitudes and motivation significantly predicted intention to use SSPPs with 55.4% and 33.4% of the variances accounted for in the data that were obtained from farmers and traders repectively. In addition, attitudes significantly mediated the relationships between plantain farmers and traders intention and their perceptions and motivation towards using SSPPs. A rigourous assessment of the structural models showed that the hypothesized model was supported by empirical data. The model had acceptable predictive relevance and ability to account for moderate to substantial variance in both data sets. iii In conclusion, postharvest interventions that aim to be successful must recognize the critical role of understanding their target audience. Technology push must be balanced with an understanding of the potential adopters’ preferences in order to attain successful and strategic solutions. In this regard it is recommended that future interventions should ascertain the perceptions held by the potential adopters prior to dissemination of solutions. The strong positive effect of motivation on behavioral intention suggests a necessity to identify and utilize peculiar factors in motivating adoption of postharvest solutions.